Desarrollo de estrategias metodológicas en el área de matemática durante el proceso de enseñanza- aprendizaje de los estudiantes de tercer año de educación general básica de la escuela “Manuelita Sáenz”, ciudad Guaranda, parroquia Gabriel Ignacio Veintimilla, provincia Bolívar, periodo 2021-2022 - Mazabanda Quiquintuña, William Patricio (2022)
This research project is oriented towards the application of knowledge in methodological strategies in the area of mathematics during the teaching- learning process of students in the third year of Basic General Education of the "Manuelita Sáenz" School, in this instance it was carried out through of an investigation process of 11 students through the structured observation sheet, a teacher with the interview and later the analysis of information was carried out to detect the problem and develop the proposal, the same one that is focused on providing a solution. Dynamic and creative activities were applied to improve the academic performance of the aforementioned students, allowing the development of three strategies focused on the area of mathematics "Problem-Based Learning, Game- Based Learning and Flipped Classroom", this depending on the institution where it is studied job. The results show that it is important to manage these methodological strategies in the area of mathematics, which allows building meaningful learning in students in an updated, dynamic and creative way. Therefore, a class becomes more dynamic when a teacher is updated and properly manages these methodological strategies to teach in the areas of mathematics, which is one of the most difficult and complex subjects